Temperature-Sensitive Template for Preparation of ZnO/CeO2 Composite Photocatalytic Materials and Its Catalytic Performance - Yaoyao Zhang; Wenjie Yang; Zhengyuan Zhu; Lin Zhang; Wenju Peng (Molecules, 2024)
In this work, a series of thermosensitive ionic liquid functionalized polymers, PNx(IL)y, with controllable morphology and particle size were prepared by free radical polymerization. Then, using the polymer PN64(IL)8 with uniform morphology as a templating agent, the ZnO composite photocatalytic materials doped with rare earth metal Ce were prepared in combination with a microwave-assisted and templated hydrothermal reaction method. Series different Ce-doping amount photocatalytic materials ZnO-Ce-x‰ were characterized by XRD, SEM, TEM, XPS, and other methods. The results demonstrated that the templated materials PN64(IL)8 can prepare ZnO-Ce-2‰ with uniform petaloid ambulacra shape, good distribution of elements, and excellent photocatalytic performance. Photocatalytic degradation experiments of methyl orange (MO) showed that when the Ce-doping amount is only 2‰, the degradation rate of organic dyes can reach 96.5% by reacting the photocatalytic materials in water for 1 h. In addition, this kind of photocatalyst can be used for the degradation of high-concentration MO, as well as being easily recovered and effectively reused by simple filtration. Therefore, the structure of this kind of photocatalyst is controllable in the preparation process with an extremely low Ce-doping amount compared with current reports, and it has a good application prospect in the field of wastewater treatment technology.